2016
DOI: 10.1016/j.trb.2016.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Creating complex congestion patterns via multi-objective optimal freeway traffic control with application to cyber-security

Abstract: This article presents a study on freeway networks instrumented with coordinated ramp metering and the ability of such control systems to produce arbitrarily complex congestion patterns within the dynamical limits of the traffic system. The developed method is used to evaluate the potential for an adversary with access to control infrastructure to enact high-level attacks on the underlying freeway system. The attacks are executed using a predictive, coordinated ramp metering controller based on finite-horizon o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(26 citation statements)
references
References 37 publications
(56 reference statements)
0
23
0
3
Order By: Relevance
“…Existing works on ITS security include case studies on traffic control wireless networks ( Ghena et al, 2014;Cerrudo, 2015 ), connected and autonomous cars ( Evtimov et al, 2017;Thing and Wu, 2016;Chen et al, 2018;Checkoway et al, 2011;Hubaux et al, 2004;Wan et al, 2016 ), ride sharing applications ( Yuan et al, 2016 ) and sensors in freeway traffic control systems ( Reilly et al, 2016;1755 ). Works ( Ghena et al, 2014;Cerrudo, 2015 ) have demonstrated that networked traffic systems are vulnerable to a variety of cyber attacks.…”
Section: Motivationmentioning
confidence: 99%
“…Existing works on ITS security include case studies on traffic control wireless networks ( Ghena et al, 2014;Cerrudo, 2015 ), connected and autonomous cars ( Evtimov et al, 2017;Thing and Wu, 2016;Chen et al, 2018;Checkoway et al, 2011;Hubaux et al, 2004;Wan et al, 2016 ), ride sharing applications ( Yuan et al, 2016 ) and sensors in freeway traffic control systems ( Reilly et al, 2016;1755 ). Works ( Ghena et al, 2014;Cerrudo, 2015 ) have demonstrated that networked traffic systems are vulnerable to a variety of cyber attacks.…”
Section: Motivationmentioning
confidence: 99%
“…For example, Reilly et al. () evaluated the impact of cyberattacks on freeway traffic using the optimal control and multiobjective optimization strategies; Amoozadeh et al. () investigated the effects of security attacks on the connected vehicle platoon by using VEhicular NeTwork Open Simulator (VENTOS) framework; and Dadras et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although much research focuses on cyberattack itself, an equally important aspect is to study the impact of malicious attacks on connected vehicles, particularly the behaviors of vehicles under cyberattack during driving. For example, Reilly et al (2016) evaluated the impact of cyberattacks on freeway traffic using the optimal control and multiobjective optimization strategies; investigated the effects of security attacks on the connected vehicle platoon by using VEhicular NeTwork Open Simulator (VENTOS) framework; and Dadras et al (2015) demonstrated that an attacker can cause the platoon to be unstable and even serious injury or death. Furthermore, Amir et al (2017) considered the stability of a platoon under a jamming attack on realistic wireless channel; and Wang et al (2018) investigated the linear and nonlinear stability of traffic flow with different cyberattacks.…”
Section: Denial Of Servicementioning
confidence: 99%
“…Physical attacks are direct attacks on the hardware. These attacks include clipping wires, theft and replacement of sensors or actuators [19]. Ghena et al [18] describe methods of attacking the hardware infrastructure of a currently deployed traffic signal system in Michigan, USA.…”
Section: Introductionmentioning
confidence: 99%